NFTs: Digital things and their criminal lives. (November 2022) - Mackenzie, Simon; Bērziņa, Diāna
The extraordinary current craze around NFTs reflects their perceived value as a technological development that can bring greater certainty to questions of ownership and authenticity in fields like art and other collectibles. This is, among other things, the promise of crime prevention through technology, as ownership and authenticity are in the art world closely tied to criminal legal matters like theft, handling stolen goods and fraud. The crime prevention promise looks to fall flat though, as the technology seems to be less capable of delivering these benefits than has been assumed by its promoters. Much of the attraction of NFTs is therefore not actually based on effective crime prevention, but rather on hype. This paper explores the hype, and its relationship to the crime prevention promise of NFTs, through the lens of 'the social lives of things'. We argue that as well as social lives, things have criminal lives. Analysis sensitive to the criminal lives of things finds an NFT trading scene heated by emotion: excitement, attraction, temptation, speculative euphoria and acquisitive, possessive sentiment. This creates a sense of object agency more active than the cold traditional vision of material structure presented in standard criminological treatments of things-in-the-world as passive opportunity structures. The hyped NFT market trades in affecting objects that create crime in emotional as well as structural ways. We therefore arrive at a conclusion opposite to starting assumptions: far from preventing crime, NFTs are making it.